Peran Pemerintah Kota Surabaya dan Masyarakat dalam Mencegah Terjadinya Tindak Kekerasan Seksual Terhadap Anak - Andrianto, Andrianto; Untari, Sri; Hady, Nuruddin (Universitas Negeri Malang, 2024)
This study aims to describe the role of the Women's Empowerment and Child Protection Service and Population and Family Planning Control with the Embun Surabaya Foundation in preventing sexual violence against children as well as obstacles and solutions in preventing sexual violence against children. This study used a qualitative approach with a case study research type. The data collection technique in this study used participant observation techniques, in-depth interviews and documentation. The data obtained are described used qualitative techniques with pattern matching. The role of the Women's Empowerment and Child Protection Service and Population and Family Planning Control in preventing sexual violence includes socialization at family learning centers, socialization of youth dynamics, and the Kampunge Arek Suroboyo Friendly to Women and Children program. The Embun Surabaya Foundation acts as a speaker in seminar activities and conducts socialization to several schools. The obstacles of the Women's Empowerment and Child Protection Service and Population and Family Planning Control in preventing sexual violence are overcome by inviting participants early, providing seminar facilities, and involving students to help participating villages compile portfolios. The obstacles of the Embun Surabaya Foundation are lack of funds and human resources which are overcome by opening volunteer vacancies and improving the objectives of the institution at the notary's office.